Telomere Length: A Potential Biomarker for the Risk and Prognosis of Stroke - Tian, Yanjun; Wang, Shuai; Jiao, Fengjuan; Kong, Qingsheng; Liu, Chuanxin; Wu, Yili (Frontiers in Neurology, 2019)
Stroke is one of the leading causes of death and disability worldwide. Age is associated with increased risk of stroke, while telomere length shortening plays a pivotal role in the process of aging. Moreover, telomere length shortening is associated with many risk factors of stroke in addition to age. Accumulated evidence shows that short leukocyte telomere length is not only associated with stroke occurrence but also associated with post-stroke recovery in the elderly population. In this review, we aimed to summarize the association between leukocyte telomere length and stroke, and discuss that telomere length might serve as a potential biomarker to predict the risk and prognosis of stroke.